2003
DOI: 10.1308/003588403321001462
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of varicose vein surgery at 10 years: clinical findings, symptoms and patient satisfaction

Abstract: Background: Data on long-term outcomes of varicose vein surgery are sparse, and 'success' rates vary substantially depending on the method of assessment. This study used a variety of methods to evaluate patients 10 years after operation. Methods: A consecutive cohort of 100 patients was identified, of whom 70 (151 operated limbs) were reviewed -50 by clinical and Doppler examination, and all by structured questionnaire. Results: A few months after operation, symptoms were 'cured' or 'much better' in 89% of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 27 publications
0
41
0
1
Order By: Relevance
“…Unfortunately, we did not use a patient-reported quality of life tool, but others have shown that despite many patients having recurrence, the majority still remain satisfied with the results from their procedure. 11,14,29 Whether these observations apply to DUS-detected recurrence after the now more prevalent endovenous procedures is an important question. The principles of vein injury response with neovascularization and vessel remodeling and venous reconnections are not unique to surgery and apply to endovascular procedures too.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, we did not use a patient-reported quality of life tool, but others have shown that despite many patients having recurrence, the majority still remain satisfied with the results from their procedure. 11,14,29 Whether these observations apply to DUS-detected recurrence after the now more prevalent endovenous procedures is an important question. The principles of vein injury response with neovascularization and vessel remodeling and venous reconnections are not unique to surgery and apply to endovascular procedures too.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term results following conventional surgical treatment are marred by significant recurrence rates. Quoted rates are as high as 30 per cent at 1 year, 40 per cent at 2 years and up to 66 per cent beyond 10 years 8 -14 ; this has been linked to poor patient satisfaction 15,16 . Patients requesting reintervention for symptomatic recurrence are less common, but approximately 15-20 per cent of varicose vein procedures are performed for recurrence 17 -19 .…”
Section: Introductionmentioning
confidence: 99%
“…The primary cause of the condition is poorly functioning valves and decreased elasticity in the vein wall, resulting in reflux (reversed flow in the vein circuit) [9]. Valve damage is the most common aetiology of primary varicose veins, leading to increased pressure and elasticity [10]. The real aetiology of these malfunctioned valves remains elusive but is likely multifactorial [11].…”
Section: Discussionmentioning
confidence: 99%